FISCAL DYSFUNCTION OF VAT ELECTRONIC INVOICING IN UKRAINE - SYNYUTKA, Nataliya; KRYSOVATA, Kateryna (Scientific journal «World of Finance», 2020)
Introduction. During 2014–2017 VAT electronic invoicing was adopted in Ukraine, which allows for the automatic exchange of tax data between taxpayers and tax authorities. It was estimated the positive impact of e-invoicing reform on gross sales and purchases, tax liabilities across all firms, tax compliance etc.Purpose. The purpose of the article is to study the impact of VAT e-invoicing on a fiscal efficiency of the tax. Methodological approaches to understand the essence and nature of the taxation of spending under the conditions of an innovative digital trend in society can be used to implement a fair fiscal policy in Ukraine.Methods. The author used scientific methods such as abstraction, deduction, comparison, analysis, systematization and others. It was used statistical data, data of tax authorities, data of the State Treasury Service of Ukraine.Results. It was established that e-invoicing in Ukraine increases VAT refund and improves its mechanism firstly. On the other hand, digital technologies positive effect on tax collection for imported goods and services in Ukraine. Despite that, the fiscal efficiency of VAT hasn`t increased.Conclusions. The lack of a positive impact of e- reform on value added tax collection in Ukraine was revealed. The main factors causing fiscal VAT dysfunction in Ukraine are: a significant shadow economy, the sale of goods and services to end-users using a simplified tax system, tax benefits for the rapidly growing agricultural sector, non-taxation of electronic goods and services. Digital tools, e-invoicing system should be supplemented by other reforms to improve revenue mobilization, enhance compliance.